Transformasi Digital Ekonomi Islam: Peran Fintech Syariah dalam Meningkatkan Inklusi Keuangan UMKM - Muhammad Natser (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study aims to analyze the effect of Islamic fintech utilization on the financial inclusion of Micro, Small, and Medium Enterprises (MSMEs) in East Jakarta. The study employed an explanatory quantitative approach with a cross-sectional survey design. Data were collected through a structured questionnaire from 150 MSME owners selected using purposive sampling and analyzed using Partial Least Squares–Structural Equation Modeling with SmartPLS. The results show that Islamic fintech utilization has a positive and significant effect on MSME financial inclusion, with a path coefficient of 0.684, a t-statistic of 11.400, and a p-value of 0.000. The R-square value of 0.468 indicates that Islamic fintech utilization explains 46.8% of the variance in MSME financial inclusion, while the f-square value of 0.880 demonstrates a substantial effect. These findings confirm that Islamic fintech services can expand access to financing, improve transaction efficiency, strengthen financial management, and increase MSME participation in the formal financial system. The study implies that governments, financial institutions, and Islamic fintech providers should strengthen digital financial education, system security, contract transparency, consumer protection, and Sharia compliance.